(untitled) (Journal of Naval Architecture and Marine Engineering, 2011)
Numerical study is performed to examine numerically the stable solution for the incompressible viscous steady flow through a curved pipe with circular cross-section. Also the combined effects of high Dean Number Dn and curvature δ on the flow are investigated. Spectral method is applied as a main tool for the numerical technique; where, Fourier series, Chebyshev polynomials, Collocation methods, and Iteration method are used as secondary tools. The flow patterns have been shown graphically for large Dean Numbers and a wide range of curvature, 0.01≤δ≤0.9.Two vortex solutions have been found for secondary flow. Axial velocity has been found to increase with the increase of Dean number and decrease with the increase of curvature. For high Dean number and low curvature almost all the fluid particles leave the inner half of the cross-section. The stable solution zone increases with the increase of curvature up to a certain limit, then decrease. DOI: 10.3329/jname.v7i1.3630